METHOD OF EVALUATION OF OBJECT-ORIENTED SOFTWARE SYSTEMS BASED ON THE ANALYSIS OF CHANGES IN THE SOFTWARE SYSTEM REQUIREMENTS - DZIURBAN, Eduard; YASHYNA, Oksana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
It is a well-known fact that software maintenance plays an important role and becomes important in the software life cycle. Since object-oriented programming has long become the standard, it is very important to understand the problems of maintaining object-oriented software systems, and how to avoid them by identifying potential gaps in the software system as early as the design analysis. This article is aimed at evaluating object-oriented systems using the analysis of changes in the requirements for the software system. The main problems raised in the article are the change of the algorithm for analyzing the impact of changing non-functional requirements on functional ones and their inheritance. The demand for efficient software is increasing day by day, and the adoption of object-oriented design of software systems is able to satisfy this demand, as it is perhaps the most powerful mechanism for developing efficient software systems. This can not only help in reducing the cost but also helps in developing high quality system software. Software developers need appropriate metrics to develop an effective software system. This practice is aimed at researching methods for evaluating an object-oriented software system using software impact analysis based on tracking requirements to changes in functional requirements using non- functional requirements. Although there are many advantages to the object-oriented approach, and the fact that this approach is the most widespread now and will be in the future, it will be truly recognized, proven and practical only when the management aspects of the software development process using of this methodology will be carefully considered. This is where software metrics play an important role, enabling better planning, evaluating improvements, reducing unpredictability, early detection of potential problems, and evaluating performance. This paper proposes a set of metrics best suited to evaluate the use of core concepts of the object-oriented paradigm, such as inheritance, encapsulation, polymorphism, and a strong emphasis on code reuse, which are uniquely responsible for increasing software quality and development productivity.